1970
DOI: 10.1042/bj1200673e
|View full text |Cite
|
Sign up to set email alerts
|

Flavin-photosensitized reactions of retinal and stilbene

Abstract: 1. Retinol and stilbene are both isomerized when they are illuminated anaerobically in the presence of flavins. 2. Triplet quenchers (e.g. oxygen, potassium iodide and paramagnetic ions) inhibit the reaction more efficiently than they quench flavin fluorescence. At 770C in a diethyl ether-isopentane-ethanol (5:5:2) glass retinol quenches flavin phosphorescence, but not its fluorescence. 3. For the stilbene reaction cis/trans photostationary-state mixtures are obtained with different flavins and these are linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…During the course of their investigations into the photochemistry of retinol derivatives in the presence of (−)-riboflavin, Walker and Radda discovered that the opposite directionality is observed (i.e., E → Z ) via sensitization in the presence of (−)-riboflavin (Vitamin B2) . The same group reported that the isomerization of stilbene can be achieved using several flavin-based derivatives . Inspired by these studies, Metternich and Gilmour developed a biomimetic isomerization in which cinnamyl derivatives serve as retinal chromophore surrogates .…”
Section: Geometric Isomerization Of Simple Alkenes Via Selective Ener...mentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of their investigations into the photochemistry of retinol derivatives in the presence of (−)-riboflavin, Walker and Radda discovered that the opposite directionality is observed (i.e., E → Z ) via sensitization in the presence of (−)-riboflavin (Vitamin B2) . The same group reported that the isomerization of stilbene can be achieved using several flavin-based derivatives . Inspired by these studies, Metternich and Gilmour developed a biomimetic isomerization in which cinnamyl derivatives serve as retinal chromophore surrogates .…”
Section: Geometric Isomerization Of Simple Alkenes Via Selective Ener...mentioning
confidence: 99%
“…163 The same group reported that the isomerization of stilbene can be achieved using several flavin-based derivatives. 164 Inspired by these studies, Metternich and Gilmour developed a biomimetic isomerization in which cinnamyl derivatives serve as retinal chromophore surrogates. 165 In an operationally simple protocol, inexpensive (−)-riboflavin was used as a photocatalyst under irradiation with violet LEDs (402 nm).…”
Section: Isomerization Of Cinnamyl Derivativesmentioning
confidence: 99%
“…25 Studies towards the flavinphotosensitization of stilbene have been undertaken, but only the trans-cis isomerisation of stilbene has been observed. 26 An example of double bond oxidation by flavin sensitization is the oxidation of unsaturated fatty acids in MeCN that yielded hydroperoxides of fatty acids. It was proposed that the oxidation proceeds by a type II (singlet oxygen) mechanism.…”
Section: Oxidation Of Phenylenesmentioning
confidence: 99%
“…[17] Stilbene (2), a prototypical substrate for studying E/Z-isomerism (Figure 1), has been a focal point in both experimental and computational investigations. [18] Experimental and…”
Section: Limitations Of the Adiabatic Modelmentioning
confidence: 99%